2015
DOI: 10.1210/en.2015-1784
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiling of GPCR Expression in Ghrelin-Producing Cells

Abstract: To determine the comprehensive G protein-coupled receptor (GPCR) expression profile in ghrelin-producing cells and to elucidate the role of GPCR-mediated signaling in the regulation of ghrelin secretion, we determined GPCR expression profiles by RNA sequencing in the ghrelin-producing cell line MGN3-1 and analyzed the effects of ligands for highly expressed receptors on intracellular signaling and ghrelin secretion. Expression of selected GPCRs was confirmed in fluorescence-activated cell-sorted fluorescently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…21 The stimulating effect of OXT on ghrelin secretion occurs via the OXT receptor in a cellular model. 22 Importantly, we document the positive effects of OXT treatment on behavior and social engagement and on mother-infant interactions. After OXT treatment, the infants were more alert, less fatigable, more expressive, and had less social withdrawal.…”
Section: Discussionmentioning
confidence: 73%
“…21 The stimulating effect of OXT on ghrelin secretion occurs via the OXT receptor in a cellular model. 22 Importantly, we document the positive effects of OXT treatment on behavior and social engagement and on mother-infant interactions. After OXT treatment, the infants were more alert, less fatigable, more expressive, and had less social withdrawal.…”
Section: Discussionmentioning
confidence: 73%
“…Other studies using the TAS1R2-lacZ knock-in mouse did not observe TAS1R2 expression in the stomach [46]. In contrast, Koyama et al showed a very low expression of TAS1R2 in the MGN3-1 cell line and primary gastric ghrelin cells using RNA sequencing [47]. However, TAS1R3 may also function as a homodimer, as previously shown on the tongue [48], in adipocytes [49] and in pancreatic β-cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…Supportive of this assertion, ghrelin secretion increases when sympathetic nerves are stimulated artificially or when adrenergic agents are infused locally into the gastric submucosa (29,30). Norepinephrine, epinephrine, and isoproterenol all stimulate ghrelin secretion from ghrelinoma cell lines and from primary cultures of gastric mucosal cells (26,(31)(32)(33)(34)(35)(36). Reserpine, which depletes norepinephrine from sympathetic Ghrelin is an orexigenic gastric peptide hormone secreted when caloric intake is limited.…”
Section: Introductionmentioning
confidence: 99%